Implementasi Perda No. 6 Tahun 2011 Tentang Pajak Reklame di Kota Semarang - A., Sri Ahmad; Marom, Aufarul; Fathurrohman, Fathurrohman (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
Advertisement tax policy is a policy that is set forth in UU nomor 28 Tahun 2009 on Regional Taxes and Regional Retribution which has the purpose, are to organize the implementation of Local Tax andRetribution give greater authority to the regions to managed and regulated the management of taxes and charges in their area. In line with big of responsibility in the area of governance and service to the community in Semarang, advertisement tax policy implementation be regulated in the regulations of the Mayor No. 973/89 of 2012 On Establishment of Regional and advertisement Class Road in Semarang city, where the presence of the Mayor of this Regulation is expected to overcome billboard problems on local taxes all this time, the problem are: the taxpayer who does not timely pay taxes, for the installation of forbidden billboards and installation of billboards do not pay attention to the aesthetics of the city. These objectives can be achieved through the implementation of effective policies that can be seen from the appropriateness of the policy, implementing accuracy, precision of the target, accuracy and precision of the process environment. Advertisement tax policy implementation in achieving its objectives can not be released from the factors that support and obstacle. Based on the theory of Van Meter and Van Horn, supporting and inhibiting factors, are Resources Policy, Communication and Implementation Activities. Characteristics Implementation Agency, Socio-Economic and Political Conditions and Disposition Implementor. 2 Based on the existing obstacles in the implementation of the advertisement tax policy in Semarang writer give some advice are : (1) giving purpose socialization and advertisement tax policy legal basis to taxpayers, so taxpayers clearly understand the rules regarding advertising tax policy. (2) firmness in giving punishment to be imposed on the taxpayer when there is infraction, whether the fraction of the taxpayer in the form of delay in paying taxes advertisement or implementation of billboards without permission. (3) conduct data collection and monitoring on a regular basis, in order to minimize the problem of illegal billboards that are not recorded in the field. (4) increasing the number of staff and staff who handle the advertisement tax policy at the Department and in the field, also increase supporting tools such as computer.